The research on the influence mechanism of entrepreneurial leadership on team creativity - Xiong, Yan (2023)
In the era of innovation and entrepreneurship, how to deal with market changes, how to seize opportunities and create value in the changes is of great significance to enterprises. Team creativity is the premise for enterprises to create value, and it has become the key for enterprises to build core competitiveness and achieve sustainable development. In this context, this research mainly studies two issues: one is the impact of entrepreneurial leadership on team creativity, that is, whether entrepreneurial leadership behavior as a fusion of entrepreneurship and leadership can effectively enhance team creativity; the second is to explore entrepreneurial leadership. The mechanism by which leadership affects team creativity, that is, to explain how entrepreneurial leadership affects team creativity.